RANCANG BANGUN APLIKASI ANDROID UNTUK MENEMUKAN LOKASI UMKM TERDEKAT DENGAN GOOGLE MAP API DAN HAVERSINE DISTANCE - Syamsu Hidayat; Astried Silvanie; Rr. Aryanti Kristantini; Rino Subekti (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
Micro, Small and Medium Enterprises (MSME), plays a role in improving people's welfare and incresing bruto income. With the support of IT for running MSMEs, it has proven to help the sustainability of MSMEs, especially during a pandemic. For this reason, we conducted a research by building a mobile applications to support MSME. This application has a minimum specification limit using Android 10 (Android Q) version. The application has the following functions (Silvanie et al., 2023) detects the current location based on GPS and Android location, (Wika Undari, 2021) displays the user's map from Google Maps and shows the user's position, (Rambe et al., 2022) retrieves UMKM data either briefly or in detail based on the closest distance to user position,(Alimuddin, 2021) the feature of registering as a member with more authority such as giving a rating. The SDLC Waterfall method is used to build the application. Calculation of the distance between the user and the MSME location is done by the Haversine formula. From the results of black box testing and the feasibility testing of the beta version, it is summarized as follows: 33% consider the application quite feasible, 66.7% consider the application feasible, 62.5% willingly to spend money to subscribe and 37.5% do not want to spend money.